eCM 2021
DOI: 10.22203/ecm.v041a19
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro effects of platelet products on the biophysiological functions of human bone marrow mesenchymal stromal cells: a systematic review

Abstract: Platelet products (PP) and bone-marrow aspirate are popular sources of osteoinductive signalling molecules and osteogenic bone marrow mesenchymal stromal cells (BM-MSCs) used in the treatment of impaired bone healing. However, the combined use of PP and BM-MSCs in clinical studies has reported mixed results. Understanding the cellular and molecular interactions between PP and BM-MSCs plays the important role of guiding future research and clinical application. This systematic review investigates the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
(298 reference statements)
0
4
0
Order By: Relevance
“… 59 Cellular therapies with osteogenic cells and osteoinductive molecules, osteoconductive scaffolds and tissue engineering are treatment strategies which holds great promise. 60 , 61 Although still in its early stages, further work on the molecular and genetic profiling of relevant tissue such as patient's serum could serve as an advantageous screening and predictive tool of fracture non‐union.…”
Section: Discussionmentioning
confidence: 99%
“… 59 Cellular therapies with osteogenic cells and osteoinductive molecules, osteoconductive scaffolds and tissue engineering are treatment strategies which holds great promise. 60 , 61 Although still in its early stages, further work on the molecular and genetic profiling of relevant tissue such as patient's serum could serve as an advantageous screening and predictive tool of fracture non‐union.…”
Section: Discussionmentioning
confidence: 99%
“…PRP remains loosely used in the literature as an all-encompassing term for any platelet-derived biologic. A recent systematic review highlighted the importance of accurately describing platelet-derived biologic, physical properties, formulation and contents to enable accurate comparison between studies [ 79 ]. The shortcomings of the existing PRP classification systems are highlighted by the lack of standardised protocols and definition for centrifugation and preparation, cellular components such as platelet concentration, red and white blood cell counts, and the procedure for platelet activation [ 80 , 81 , 82 , 83 , 84 , 85 ].…”
Section: Platelet-rich Plasma (Prp)mentioning
confidence: 99%
“…Allogeneic platelet lysate or PRP prepared from young, healthy donors has a great potential enhancing chondrogenic and osteogenic potential of MSCs. This combination therapy is popularly considered for traumatic bone damage and various degenerative joint diseases [27,28]. In a case study, a combined local injection of adipose tissue-MSCs with platelet-rich plasma showed satisfactory outcomes in an experimental model of femoral head ON [29].…”
Section: Pre-clinical Studiesmentioning
confidence: 99%